Fabrication of hybrid zno/tips-pentacene organic based diode using spray coating technique - Dzul Fahmi Mohd Husin Seria (2019)
Organic material is one of the main attraction in recent electronic device applications for smartphone, tablet, and computer due to its high mobility, air stability, and solution processability. This will allow researchers to focus on organic semiconductor in order to achieve the aim for large area application, light weight, and mechanically flexible. This thesis describes analysis and characterization of hybrid ZnO/TIPS-Pentacene organic based diode using several deposition techniques such as drop, dip and spray coating technique. TIPS-Pentacene powder was diluted with Dichloromethane, Chloroform, and Toluene to form weight percentage of 0.1wt%, and 0.2wt%. Disposable spray bottle and airbrush spray were used to analyze the spraying pattern droplet effect to achieve crystalline TIPS-Pentacene thin film. Airbrush spraying technique was chosen as the deposition technique as it can be applied for large coverage and edge area, roll-toroll process and even thickness. Analysis dependence of deposition parameter was performed to find optimum thin film quality such as distance from nozzle to substrate, number of spray passes and inlet gas pressure used. Optimum distance from nozzle tip to substrate distance was 10 cm with 10 spray passes and 10psi of gas pressure. The thin films were investigated by X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM) and surface profilometer to reveal the film molecular and structure orientation. The spray coated thin films exhibited (0 0 I) diffraction peaks at 5.34° with d-separation of 16.4 A that comparable to thermal evaporation method. The surface roughness of deposited thin films varies from 48.7nm to 158nm and grain boundaries between 7nm to 8nm. Following with that, an organic device was fabricated in order to investigate the electrical characteristics. The device structure of rromPSPentacene/ Al with 0.1 and 0.2 wt% was constructed and exhibited non-linear behaviour at a low voltage while linear behaviour at a high voltage which similar to conventional p-n junction diode. Furthermore, analysis of electrical characteristics was done to investigate the device performance. The ideality factor (n) and barrier height (<l>b) at different wt% found to be 14.62 and 13.25, 1.leV and 1.48 eV respectively. Hyrbid diode was fabricated with different device architecture of ITO/TIPS-Pentacene/ZnO/ Au, rromPS-pentacene/ZnO and ITO/ZnOmPSPentacene. ITO/TIPS-Pentacene/ZnO/ Au was found to show excellent electrical characteristic among others with low turn on voltage of 0.SSV, small value of ideality factor (11.53) and barrier height (1.19eV). Spray coating technique can be the alternative technique for solution process and applied for roll-to-roll device fabrication with desired quality of thin film and good electrical performance.